(untitled) (Archives of Criminology, 2023)
In the activities carried out towards prisoners, concern for their safety is the key role in the implemented system of pre-suicidal prevention. The manuscript describes a list of risk factors identified in the literature that may be important in the correct estimation of the suicide risk assessment. Therefore, the preventive procedures developed in the polish prison system, are focused on monitoring and early identification of suicidal risk factors for inmates. Diagnosis and classification of inmates to the risk group triggers a series of preventive actions taken in prison. Their implementation contributes to limiting the occurrence of the phenomenon of suicides in penitentiary isolation. The subject of the research described in the manuscript is the characteristics of successful suicides in isolation in 2015–2019. The analysis of data from the group of suicides (N = 114) in terms of suicidal risk indicators allowed to identify many aspects of the suicidal process in penitentiary isolation in Poland. Many presented variables were estimated, including temporality of the phenomenon, selected penitentiary characteristics of suicides and data on responsibility for the occurrence of the event. The obtained results provide useful data that may be used to improve the diagnosis system and early identification of prisoners at risk of suicide.